The Perceptions of Irish Mathematics Teachers Toward a Curriculum Reform 5 Years After Its Implementation - Johnson, Patrick; Freemyer, James Vincent; Fitzmaurice, Olivia (Frontiers in Education, 2019)
In Ireland the discussion about the educational goals of a curriculum have often been subsumed by the headlong rush to meet targets defined by state examinations, with the unfortunate consequence that the state examinations have often come to define the goals of the curriculum. In 2010 a new nationwide post-primary mathematics curriculum, locally titled ‘Project Maths’, was introduced in an attempt to modernise a perceived out-dated curriculum by simultaneously altering the content of the curriculum, the pedagogical approaches employed by teachers, and the national assessment strategies. There was the belief by policy makers that only by altering all three of these curricular pillars concurrently could they definitively remove the prevailing approach of “teaching to the test”. This study aims to investigate teachers’ perceptions towards the implementation of this new curriculum five years after it was rolled out. A cross-sectional, mixed-methods research approach, that collected both qualitative and quantitative data, was employed via a nationwide survey of current mathematics teachers. Responses from 147 teachers indicated that for the most part teachers are supportive of the new curriculum goals, but that they are still struggling regarding the implementation of the intended curriculum in the classroom.